If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 3x + 1 = 7 Reorder the terms: 1 + x + 3x = 7 Combine like terms: x + 3x = 4x 1 + 4x = 7 Solving 1 + 4x = 7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 4x = 7 + -1 Combine like terms: 1 + -1 = 0 0 + 4x = 7 + -1 4x = 7 + -1 Combine like terms: 7 + -1 = 6 4x = 6 Divide each side by '4'. x = 1.5 Simplifying x = 1.5
| x^2-2x=60+2x | | x+20=4x+2 | | (2x+3)(x-5)=4x+6 | | 2f-5=5f+22 | | 5=10+4.9x-4.9(x^2) | | x-23=71 | | y^2-6y+9=2y-10 | | 5x+10=4x+9 | | -3.4p+5.8-97p+0.40+5.8p= | | -p=-2p-2 | | 14/xy^2-1y2/8x^2 | | 5x^2+30x-60=0 | | 2x^2-480=0 | | m13/3 | | a=3a-8 | | 4(7)-3(6)/9= | | 3(y-1)=9-2(-7y-3) | | 40x^3-35x^2+8x-7= | | 2-5x=3x-5 | | 126=-16x^2+90x | | f(x)=x^2-10x-600 | | x^2-3+x=-21 | | 126=-16x^2+90t | | 430/x=.25 | | (5y-9)(1+y)=0 | | 1-7lnx=0 | | 5r-10=4r | | g(x)=x^2-10x-600 | | 1.2=(x/x-750) | | g(x)=x^2-10x-6000 | | -2(u+5)=4u-6+4(3u+1) | | 2y=y+-1 |